ANALISIS RASIO RENTABILITAS UNTUK MENGETAHUI KINERJA KEUANGAN PADA PT. BANK MANDIRI (PERSERO) TBK - Dwi Fadhilah Umami; Yasya Fitria Apsari; Muhammad Falah Musyaffa; Renny Oktavia (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
. This study aims to estimate and evaluate the profitability comparison of PT Bank Mandiri in terms of Return On Asset (ROA), Return On Equity (ROE) and Net Profit Margin (NPM) at Bank Mandiri in 2020-2021. Research methodology is carried out by reviewing a number of scientific books, journals, papers, and articles relevant to current discussions. Financial statement data is obtained from Bank Mandiri's website. The analysis method used, namely by quantitative and qualitative. The results obtained by Bank Mandiri's Return on Asset (ROA) value in 2020 were 1.57% which were in Good condition while in 2021 Bank Mandiri's ROA value was 2.34% which was in Very Good condition. The Return On Equity (ROE) value at Bank Mandir in 2020 was 8.05% which indicates the undesirable category. Meanwhile, in the 2021 period, it faced an increase in Bank Mandiri's Retrun On Equity value of 13.39%, which showed that it was in the Sufficient category. In 2020, Bank Mandiri's NPM was 170.96%, indicating very good conditions. However, in 2021 Bank Mandiri's NPM decreased where in 2021 Bank Mandiri's NPM was 30.36% which showed very bad conditions